EVALUASI KINERJA STRUKTUR GEDUNG KLINIK YULIANA MANOKWARI DENGAN ANALISIS BEBAN DORONG - Veronika Y Ohoilulin; Yoga Charol Vincenthius Tethool; Radinal Bakri (TEKNIKA: Jurnal Teknik, 2023)
Manokwari City is the capital of West Papua Province and one of the provinces in Indonesia that faces a high risk of earthquakes. Therefore, earthquak resistant building structures are planned to reduce the risk of damage caused by earthquakes. Steel construction is one alternative structures used in medium to high rise buildings. In the development of earthquake resistant building, one of the methods used is performance based design with the pushover analysis, which can determine the structural collapse behavior due to earthquakes. This study focused on the Yuliana Manokwari Clinic Building, which was evaluated using a special concentric braced frame (SCBF) structure system with pushover analysis based on FEMA 440 and ATC-40. Based on the analysis and calculations carried out, the main beam dimension used was WF 300×200×8×12×18, column dimension was H 400×400×30×50×22, and bracing dimension was SHS 180×180×10×10×18. The capacity curve obtained was a lateral force value in the X direction of 14653.18 kN and a displacement of 0.152 m, and in the Y direction of 16155.45 kN and a displacement of 0.221 m. The structural performance level obtained was in the immediate occupancy (IO) and damage control (DO) categories. The damage index commentary obtained was that the structural performance level was moderate, and the dominant plastic hinge occurred in the bracing and beam. This indicates that the Yuliana Manokwari Clinic Building did not experience significant structural damage, and the risk of casualties was very low. Keywords: Earthquake, Pushover Analysis, Steel Structure, Structural Performance, Plastic Hinge.